Fertility responses and hormone profiles of synchronized different breed of cows from different farming systems / Syafnir - Syafnir, Syafnir (2012)
The objectives of this study were to determine the efficiency of controlled internal drug release (CIDR) to synchronize estrus in cow, and to study the success rate of estrus synchronization and fertility responses with respect to animal’s breed, farming system and body condition score (BCS). The study was conducted between January 2007 to December 2008 in three private farms in Gua Musang, Kelantan. The cows aged between 3 to 7 years old were of Charolais crossbreds (n=52), Brahman crossbreds (n=13) and Kedah-Kelantan (n=37) breed. All cows were subjected to estrus synchronization with CIDR. On day 0, CIDR implant with estradiol benzoate capsules were inserted into the vagina of the cow. On day 8, estradiol benzoate was injected, 24 hours prior to insemination with frozen semen provided by the Department of Veterinary Services, Kelantan. Blood samples (10 ml) were collected by using jugular venipuncture on day 0, 3, 7, 8, 9, 12 and 14 of the experiment. Pregnancy diagnosis was carried out on day 60 post-insemination by rectal palpation. Body Condition Score (BCS) for cows in intensive farm (4.59±0.22) was significantly higher (p<0.05) when compared to cows in semi-intensive (3.76±0.14) and integration farms (3.42±0.12). Cows in Intensive (59%) and semi-intensive (59%) farms showed significantly higher percentage of pregnancy for fixed time insemination than that of cows in integration farm (37%). Charolais crossbreds breed had better BCS (4.65 ± 0.18) than Brahman crossbreds (4.03 ± 0.11) and Kedah-Kelantan (3.43 ± 0.09) bred, respectively. Charolais crossbreds showed significantly higher percentage of pregnancy to fixed time insemination (58%) when compared to Brahman crossbreds (54%) and Kedah-Kelantan (49%) bred (p<0.05). The percentage of pregnancy for cows with BCS 4 (53%) and 5, 6, 7 (69%), were significantly higher than cows with BCS 3 (43%). Cows with ≥ 55 days of postpartum interval had significantly higher percentage of the estrus (75%) and pregnancy (62%) than cows with < 55 days of postpartum interval. On day 0, progesterone level was 3.16±0.74 ng/ml for all bred of cows and reached the peak on day 3 (12.75±1.21 ng/ml). Level of progesterone started to decline on day 3 and the lowest level was observed on day 12 (1.37±0.48 ng/ml). Progesterone levels on day 0 were 7.47±1.13 ng/ml, 0.52±0.09 ng/ml, and 3.13±0.92 ng/ml, for Charolais crossbreds, Brahman crossbreds and Kedah-Kelantan breeds, respectively. Progesterone level was highest on day 3 for Charolais crossbreds (6.21±1.25 ng/ml), Brahman crossbreds (9.03±3.73 ng/ml) and Kedah-Kelantan (27.16±5.36 ng/ml). On day 0, estradiol level was 3.27±0.55 pg/ml for all bred of cows and reached the peak on day 9 (43,47±7.88 pg/ml). Estradiol levels were 0.00±00 pg/ml, 5.01±0.90 pg/ml, and 4.60±0.61 pg/ml, for Charolais crossbreds, Brahman crossbreds and Kedah-Kelantan breeds, respectively on day 0. Estradiol level was highest on day 9 for Charolais crossbreds (77.26±1.89 pg/ml), Brahman crossbreds (34.20±1.48 pg/ml) and KedahKelantan (27.47±4.91 pg/ml) bred.